Detection of Fusarium oxysporum f.sp. lactucae race 1 and 4 via race-specific real-time PCR and target enrichment - Mestdagh, Hanna; Van Poucke, Kris; Haegeman, Annelies; Dockx, Tinne; Vandevelde, Isabel; Dendauw, Ellen; Decombel, An; Höfte, Monica; Heungens, Kurt (Frontiers in Plant Science, 2023)
Fusarium oxysporum f.sp. lactucae (Fol) causes a vascular disease in lettuce that results in significant yield losses. Race-specific and sensitive real-time PCR assays were developed for Fol races 1 and 4, which are prevalent in Europe. Using genotyping-by-sequencing, unique DNA loci specific to each race were identified and subsequently used for the design of primers and hydrolysis probes. Two assays per race were developed to ensure specificity. The two assays of each race could be run in duplex format, while still giving a sensitivity of 100 fg genomic DNA for all assays. Sample preparation methods were developed for plant tissue, soil, and surfaces, with an extra enrichment step when additional sensitivity was required. By controlling the incubation conditions during the enrichment step, the real-time PCR signal could be matched to the number of spore equivalents in the original sample. When enriching naturally infested soil, down to six conidiospore equivalents L -1 soil could be detected. As enrichment ensures sensitive detection and focuses on living Fol propagules, it facilitates the evaluation of control measures. The developed detection methods for soil and surfaces were applied to samples from commercial lettuce farms and confirmed the prevalence of Fol race 4 in Belgium.Monitoring of soil disinfestation events revealed that despite a dramatic decrease in quantity, the pathogen could still be detected either immediately after sheet steaming or after harvesting the first new crop. The detection method for plant tissue was successfully used to quantify Fol in lettuce inoculated with race 1, race 4 or a combination of both. Under the temperature conditions used, race 4 was more aggressive than race 1, as reflected in larger amounts of DNA of race 4 detected in the roots.These newly developed assays are a promising tool for epidemiological research as well as for the evaluation of control measures.